PERMAINAN BONEKA TANGAN KREATIF UNTUK MELATIH KEMAMPUAN EKSPRESIF DALAM ASPEK BAHASA - Balqis; Asmita, Cici; Halifah, Syarifah; Tadzkirah (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research aims to train expressive skills in the language aspect with creative hand puppet games in group B at Al-Imaniah Kindergarten, Parepare City, where the results of the researcher's initial observations saw that there were several children who were developing their language skills, especially expressive language which had not yet developed optimally. This research uses qualitative research methods with a descriptive approach. Data collection techniques use observation, interviews and documentation. The research results showed that before the creative hand puppet game was implemented, there were several children who had not been able to develop their expressive language skills. After the researchers implemented the creative hand puppet game using the fairy tale storytelling method, there was an increase in children who previously did not know about expressive language and became knowledgeable. From the results of this activity, the researcher concluded that there was development of expressive language with creative hand puppet games, where all assessment indicators improved.